2007
DOI: 10.1080/21528586.2007.10419166
|View full text |Cite
|
Sign up to set email alerts
|

Investing in discourses of poverty and development: How white wealthy South Africans mobilise meaning to maintain privilege

Abstract: Twelve years after the transition from apartheid to democracy, South Africa remains a severely unequal society. On the one side of the divide are relatively prosperous white South Africans and an increasing black middle and upper class; and on the other side are harshly poor black South Africans. Despite decreasing interracial inequality, many white South Africans remain in a highly privileged position at the intersection of continued race and class systems of privilege. Research on whiteness in South Africa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…As it is the rest of the world, the concept of race is complex. It is supported by and intertwined with systems of class and nation (Collins ; Morning ; Wale and Foster ). In this case, they interpreted interactions through assumptions rooted in their Western socializations.…”
Section: Importing and Modifying Racementioning
confidence: 99%
“…As it is the rest of the world, the concept of race is complex. It is supported by and intertwined with systems of class and nation (Collins ; Morning ; Wale and Foster ). In this case, they interpreted interactions through assumptions rooted in their Western socializations.…”
Section: Importing and Modifying Racementioning
confidence: 99%
“…Accordingly, different studies identified discourses used by white South Africans to resist change and maintain privilege. One discourse invokes the notion of non-racialism as colour-blindness, or a disregard for "race" based on a perception that "race" is not related to advantage or disadvantage (Steyn, 2001;Wale & Foster, 2007). For example, reverse racism is a term used by white medical students in describing affirmative action measures, which admit black students to university with lower marks, as constituting an unfair and discriminatory advantage (Erasmus & De Wet, 2003).…”
Section: Discourses Of Dominancementioning
confidence: 99%
“…Africans to ignore the structural inequalities and institutional racism which maintain their privilege and power (Steyn, 2001;Wale & Foster, 2007) and the exclusion of black students (Kessi & Cornell, under review).…”
Section: Discourses Of Dominancementioning
confidence: 99%
See 2 more Smart Citations